CURRENT STATE OF FLORA IN THE ZONE OF INFLUENCE OF DUMP "2-3" OF PJSC "ARCELORMITTAL KRYVYI RIH". (Ecological Bulletin of Kryvyi Rih District, 2025)
The plant communities adjacent to the dumps, in contrast to the plant communities of the dumps, are poorly studied from a floristic point of view and require in-depth research to establish the species composition of plants. Such studies will allow us to establish the peculiarities of the taxonomic composition of plant communities formed between dumps and agricultural areas. We conducted a study of the taxonomic composition of plant communities in the area affected by the "2-3" OF PJSC "ARCELORMITTAL KRYVYI RIH" near the village of Stepove. The species composition was determined at 42 sample plots around the dump. It was found that the current species composition of plant communities in the 2-3 dump area consists of 97 species of angiosperms from 36 families. The plant communities include 28 species of trees and shrubs belonging to 16 families. The Red Data Book of Ukraine includes the following species: Morchella steppicola Zerova, Muscari neglectum Guss. Ex Ten., Stipa capillata L., Amygdalus nana L., Thymus dimorphus Klokov et Des-Schost.. The Regional List of Protected Plants of Dnipropetrovska oblast includes 3 species - Amygdalus nana L., Thymus dimorphus Klokov et Des-Schost. Muscari neglectum Guss. Ex Ten. Thus, the flora of the waste heap impact zone formed as a result of the processes of self-overgrowth has signs of steppe and is represented mainly by wild species of the steppe florocoenotype.
Keywords: dump, dump flora, taxonomic spectrum